Automatic Control with Experiments - Hernández-Guzmán, Victor Manuel; Silva-Ortigoza, Ramón; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook presents theory and practice in the context of automatic control education. It presents the relevant theory in the first eight chapters, applying them later on to the control of several real plants. Each plant is studied following a uniform procedure: a) the plant's function is described, b) a mathematical model is obtained, c) plant construction is explained in such a way that the reader can build his or her own plant to conduct experiments, d) experiments are conducted to determine the plant's parameters, e) a controller is designed using the theory discussed in the first eight chapters, f) practical controller implementation is performed in such a way that the reader can build the controller in practice, and g) the experimental results are presented. Moreover, the book provides a wealth of exercises and appendices reviewing the foundations of several concepts and techniques in automatic control. The control system construction proposed is based on inexpensive, easy-to-use hardware. An explicit procedure for obtaining formulas for the oscillation condition and the oscillation frequency of electronic oscillator circuits is demonstrated as well.
Chapter 1: Introduction -- Chapter 2: Physical system modeling -- Chapter 3: Ordinary linear differential equations -- Chapter 4: Stability criteria and steady state error -- Chapter 5: Time response-based design -- Chapter 6: Frequency response-based design -- Chapter 7: The state variables approach -- Chapter 8: Advanced topics in control -- Chapter 9: Feedback electronic circuits -- Chapter 10: Velocity control of a PM brushed DC motor -- Chapter 11: Position control of a PM brushed DC motor -- Chapter 12: Control of a servomechanism with flexibility -- Chapter 13: Control of a magnetic levitation system -- Chapter 14: Control of a ball and beam system -- Chapter 15: Control of a Furuta pendulum -- Chapter 16: Control of an inertia wheel pendulum -- A: Fourier and Laplace transforms -- B: Bode diagrams -- C: Decibels, dB -- D: Magnetically coupled coils -- E: Euler-Lagrange equations subject to constraints -- F: Numerical implementation of controllers -- G: MATLAB/Simulink code used for some simulations -- Index.
Keywords: Control engineering; System theory; Control theory; Electric power production; Industrial engineering; Production engineering; Control and Systems Theory; Systems Theory, Control; Electrical Power Engineering; Industrial and Production Engineering